Efektivitas Metode Pembelajaran Kelompok Untuk Meningkatkan Keterlibatan Siswa dalam Materi Tata Surya di SMPN 2 Kejayan pada Kurikulum Merdeka - Agung Suci Dian Sari; Nurul Hidayah Al Mubarokah; Anis Sulalah; Mohammad Zaky Tatzar; Niyatul Hasanah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This research aims to determine the effectiveness of the group learning method to increase student involvement in studying the solar system at SMPN 2 Kejayan in the Merdeka Curriculum. The group learning method is applied as an alternative to conventional learning methods. This research was carried out at SMPN 2 Kejayan, which is located in Wrati Village, Kejayan District, Pasuruan Regency, East Java Province. The research was conducted in the even semester of the 2022/2023 academic year in classes 7A, 7B, and 7C. Each class is divided into 5 groups consisting of male and female students. The number of students involved in this research was 75 students. Data collection techniques were carried out through classroom observation instruments. Observation instrument to measure student involvement by directly observing learning activities using group learning methods. The observation instrument uses an observation sheet. Observation instruments are used to observe students in aspects of carrying out group assignments, students in answering questions, students actively participating in groups, and students responding to teacher explanations. The research results show that the group learning method is effective in increasing student involvement in studying the solar system with the average percentage of student involvement in the group learning method being 81.25%. Students who use group learning methods show higher levels of engagement, better understanding, and positive perceptions of learning.